Affective computing: Knowing how you feel / Mohd Hafiz Mohd Hassin, Azizi Ab. Aziz and Norita Md. Norwawi - Mohd Hassin, Mohd Hafiz; Ab. Aziz, Azizi; Md. Norwawi, Norita (2004)
Current state of the art in computer science is an attempt to build a system that understands us. Affective computing is one of the attempts made to build an information system that can detect, classify, and respond to human emotion. Affective computing is a combination of artificial intelligence and cognitive science that inspired researcher to build a computer system or robot that similar to Commander Data in Star Trek fiction movie. This paper discusses the general architecture and applications of affective computing.